2013
DOI: 10.1007/s10495-013-0956-x
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 ameliorates oxidative stress and prevents mitochondrial alteration in ischemic retinal injury

Abstract: Coenzyme Q10 (CoQ10) acts by scavenging reactive oxygen species for protecting neuronal cells against oxidative stress in neurodegenerative diseases. We tested whether a diet supplemented with CoQ10 ameliorates oxidative stress and mitochondrial alteration, as well as promotes retinal ganglion cell (RGC) survival in ischemic retina induced by intraocular pressure elevation. A CoQ10 significantly promoted RGC survival at 2 weeks after ischemia. Superoxide dismutase 2 (SOD2) and heme oxygenase-1 (HO-1) expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
64
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 68 publications
5
64
0
Order By: Relevance
“…Modulating mitochondrial integrity, such as by inducing DRP1 inhibition or CoQ 10 treatment, has been shown to rescue RGCs in glaucoma. 31,61,62 Mitochondrial dysfunction, in turn, affects the NAD/NADH levels and here we observed downregulation of certain key redox regulatory enzymes in response to high IOP exposure, such as aldehyde dehydrogenase, enolase, aldose reductase, acyl dehydrogenase, and phosphoglycerate dehydrogenase. We have previously reported downregulation of 13 subunits of the NADH dehydrogenase: ubiquinone oxidoreductase complex 1 in the human POAG, and these findings together may reflect a failure of the tissues to maintain redox homoeostasis in glaucoma.…”
Section: Discussionmentioning
confidence: 53%
“…Modulating mitochondrial integrity, such as by inducing DRP1 inhibition or CoQ 10 treatment, has been shown to rescue RGCs in glaucoma. 31,61,62 Mitochondrial dysfunction, in turn, affects the NAD/NADH levels and here we observed downregulation of certain key redox regulatory enzymes in response to high IOP exposure, such as aldehyde dehydrogenase, enolase, aldose reductase, acyl dehydrogenase, and phosphoglycerate dehydrogenase. We have previously reported downregulation of 13 subunits of the NADH dehydrogenase: ubiquinone oxidoreductase complex 1 in the human POAG, and these findings together may reflect a failure of the tissues to maintain redox homoeostasis in glaucoma.…”
Section: Discussionmentioning
confidence: 53%
“…Many animal studies have provided promising results for Co-Q10's neuroprotective effects in glaucoma models; It has been demonstrated that intraocular and oral Co-Q10 reduces RGC apoptosis [49], and ameliorates oxidative stress mediated mitochondrial dysfunction in a rat OHT model [50]. Co-Q10 can also reduce damage from glutamate excitotoxity, and promote RGC survival by preserving optic nerve head axons in glaucomatous mice [51].…”
Section: Coenzyme Q10mentioning
confidence: 99%
“…). Its end products (e.g., coenzyme Q10, prenyls, and cholesterol) are essential for neuronal function [Lee et al, ; Segatto et al, ; Villarroel‐Campos et al, ]: cholesterol, for example, is a key component of the myelin sheath and of neuronal membranes in axons, dendrites, and synapses [Orth and Bellosta, ]. It must be synthesized within the brain as the blood‐brain barrier prevents import of lipoproteins, but the cellular origin of the different pools in neurons are incompletely understood [Pfrieger and Ungerer, ; Segatto et al, ].…”
mentioning
confidence: 99%